Stenotrophomonas maltophilia, a Pathogen of Increasing Relevance to Dermatologists: A Case Report and Review of the Literature - Annika Belzer; Emma Weiss; Farshid Etaee; Christopher G. Bunick; William Damsky; Caroline A. Nelson (MDPI AG, 2022)
Stenotrophomonas maltophilia is a Gram-negative bacillus that causes skin and soft tissue infections (SSTI), as well as bacteremia, pneumonia, and urinary tract infections. S. maltophilia infections are typically nosocomial and are often transmitted through water sources. Although historically described in immunocompromised hosts, S. maltophilia prevalence is increasing in both immunocompromised and immunocompetent populations. In light of high morbidity and mortality, it is critical that dermatologists are aware of this organism because of the limited options for therapy. Here, we describe a case of a S. maltophilia abscess with bacteremia in a patient with chronic lymphocytic leukemia and aplastic anemia that was successfully treated with trimethoprim-sulfamethoxazole. We also review the current standard of care and propose an algorithm for the treatment of S. maltophilia infection.